(3GdMTGFT dOjSbhQjOhSs - (3Mfjf Hf ESMGb , CHh RjO Mfjf Hf ESMGb GdYHGOj,J (B260 (3g` s ((3Ydi GNJjGQ Hf MSjf NQGSGfj s)
(3ChdgG (B:s
(3GdHGH GdChd aj PcQ eG jMJGL Edjg MGd GdGYVGA HMSH JQJjHgG aj GdhVY heG jYQV dcd hGMmO efgG aj WHGYI s
(3BNQgG (B:s
(3TLQI GdJjf TLQI Jchf HeUQ s
(3eYg JQLeI aGQSjI ddcJGHs
(3hHgG UhQ ddHYV GdGYTGH hGdfHGJGJ GdeJYdbI HGdcJGHs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B287 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B87s
Keywords: (3GdWHs